Generation of Uniform Hazard Spectrum Based on the Stochastic Method of Simulating Ground Motion and Its Use in Nuclear Power Plants - Xueming Zhang; Weiming Yan; Haoxiang He; Yunlun Sun; Shicai Chen (Advances in Civil Engineering)
To obtain an accurate uniform hazard spectrum (UHS), this paper proposes combining a stochastic simulation with probabilistic seismic hazard analysis. The stochastic method fully accounts for the effect of the source mechanism, path, and site effect. Historical ground motions in the site specific to the nuclear power plant (NPP) are simulated, and a UHS with an equal exceeding probability is proposed. To compare the seismic performance of the NPP under different ground motions generated by the existing site spectrum (SL-2), the UHS generated by the safety evaluation report, and the US RG1.60 spectrum, respectively, a three-dimensional finite element model is established, and dynamic analysis is performed. Results show that the structural responses to different spectra varied; the UHS response was slightly larger than that of RG1.60. This finding is relatively more reasonable than prior research results. The UHS generated using the stochastic simulation method can provide a reference for the seismic design of NPPs.